The Effect of Moringa-Chayote Decoction on Breast Milk Production and Infant Weight Gain: Pengaruh Rebusan Daun Kelor dan Labu Siam terhadap Produksi ASI dan Kenaikan Berat Badan Bayi - Asni Annisa Siregar; Rasmin Hi Abdul Mutalib (Poltekkes Kemenkes Palu, 2026)
Background: Perceived or actual low milk production can undermine continued breastfeeding. Moringa is widely used as a food-based galactagogue, whereas direct evidence for chayote and for a combined preparation remains limited. This study examined the association of a moringa leaf–chayote decoction with expressed breast milk volume and infant weight gain. Methods: A quasi-experimental pretest–posttest control-group study was conducted among 14 breastfeeding mothers at the Kalumata Community Health Center, Ternate City. Participants were assigned to an intervention group (n = 7), which consumed 250 g of boiled moringa leaves and chayote, or a control group (n = 7), which received no intervention. Breast milk volume and infant weight were measured at baseline and every seven days over 30 days. Changes between the two groups were analyzed using an independent-samples t-test. Results: The intervention group showed a more favorable distribution of change in expressed breast milk volume. Three mothers (42.9%) had an increase greater than 40 mL, whereas six mothers (85.7%) in the control group had increases of 20 mL or less. The originally reported between-group difference was statistically significant (p=0.001). Infant weight gain was also more favorable in the intervention group (p=0.006). Participant-level continuous records were unavailable for additional analysis; therefore, means, standard deviations, confidence intervals, test statistics, and effect sizes could not be calculated. Conclusion: Within this small, non-randomized sample, consumption of the combined moringa leaf and chayote preparation was associated with greater reported increases in expressed breast milk volume and infant weight. These findings should be regarded as preliminary and require confirmation in adequately powered randomized studies with standardized intervention and outcome-measurement procedures.